PDTM-20. THE HISTONE MUTATION H3.3-G34R ENCOUNTERED IN PEDIATRIC HIGH GRADE GLIOMA MODIFIES THE TUMOR IMMUNE MICROENVIRONMENT RENDERING IT MORE PERMISSIVE FOR IMMUNE MEDIATED THERAPIES. (11th November 2019) - B Garcia-Fabiani, Maria; Kadiyala, Padma; Haase, Santiago; Alghamri, Mahmoud; Comba, Andrea; Nunez, Felipe; Whalen, Matthew; Lowenstein, Pedro; Castro, Maria
Abstract: Pediatric high grade gliomas (pHGGs) have a median survival (MS) of 9–15 months and are the most common malignant brain tumors in children. No significant improvement in the MS of these patients has been registered in decades. Thus, a representative in vivo model to study these tumors is critical. Recurrent mutations in genes encoding histones H3.3 and H3.1 have been described, which are distinctive of pHGGs. To stablish a mouse model for pHGG harboring the mutation H3.3-G34R, which co-occurs with inactivating mutations in ATRX and TP53, we used the Sleeping Beauty transposase system (H3.3-G34R group). The MS of mice harboring H3.3-G34R mutation was significantly longer than the MS of the WT-H3.3 control group (p< 0.0001). We performed RNA-Sequencing of these tumors which yielded 233 differentially expressed genes between these two groups (p< 0.05). Gene set enrichment analysis of the upregulated genes in H3.3-G34R group showed significant GOs related to immune response activation and response to IFNγ. Thus, we next studied the tumor microenvironment (TME) to determine the distinctive immune cell populations, at the phenotypic and functional level. We observed that the H3.3-G34R TME exhibited less frequency of Gr-1+/CD11b+ cells (myeloid-derived suppressor cells: MDSC). MDSC are immature myeloid cells that impair T cell functions and the adaptive immune response. Moreover, the H3.3-G34R TME had increased numbers of total macrophages (p< 0.05), a higher proportion of M1 anti-tumor macrophages, and higher levels of CD8+ T cells (p< 0.01). Also, the H3.3-G34R renders glioma cells more sensitive to IFNγ regulation as it induced a higher pSTAT1/STAT1 ratio in H3.3-G34R cells. These results shed light on the interaction between the immune system and the H3.3-G34R glioma cells and how this could be harnessed to develop immune mediated therapies specific for pHGG harboring the H3.3-G34R mutation.